Struktur Komunitas Teripang (Holothuroidea) di Pantai Elak-Elak Sekotong Lombok Barat - Siskawati; Rahman, Ibadur; Astriana, Baiq Hilda (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Sea cucumbers are marine animals of the holothuroidea class (phylum Echinoderms), which are natural decomposers and play an important role in maintaining aquatic ecosystems. Sea cucumbers can clean up the remnants of organic matter on the seafloor, so that they can maintain the balance of nutrients in an ecosystem. This study aims to determine the species composition and structure of sea cucumber communities, including: abundance, diversity index, uniformity index, and dominance index, as well as to determine the influence of environmental parameters on the abundance of sea cucumber species. Sea cucumber data collection was carried out using the transect belt method, with a transect length of 100 m and a width of 1 meter to the left and 1 meter to the right, respectively, so that a total monitoring area of 200 m2 was obtained. At station 1, the width of the beach is less than 100 meters, so the area of the observation area is adjusted to these conditions. 6 species of sea cucumbers were found, namely: Synapta maculata, Opheodesoma grisea, Chirota smirnovi, Holothuria leucospilota, Actinopyga alboniger, Holothuria scabra. The total abundance value of sea cucumbers found in the waters of Elak-Elak Beach ranges from 164-172 ind/ha. S. maculata is the species with the largest abundance value, ranging from 500-883 ind/ha, while the species with the smallest abundance value are A. alboniger and H. scabra, at 17 ind/ha. Environmental parameters affect the abundance of sea cucumbers, where more sea cucumbers are found in habitats with muddy sand substrates and seagrass vegetation.